2001
DOI: 10.1253/jcj.65.617
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation of the Onset of Acute Myocardial Infarction in the Osaka Area, 1998-1999

Abstract: he time of onset of acute myocardial infarction (AMI) has a characteristic circadian variation, 1-10 with a definite morning peak and a vague evening peak. [7][8][9][10] Analysis of this circadian variations is important to clarify the triggering mechanisms of AMI.Although the precise underlying mechanisms of the circadian variation of AMI are still unclear, the morning peak appears to be associated with surges of blood pressure, 11-13 neurohumoral factors 14,15 and platelet aggregability; [16][17][18] that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 19 publications
2
24
0
5
Order By: Relevance
“…However, the subjects registered in the study can be considered representative of the AMI population in the Osaka area, because more than one-third of all AMI patients in Osaka were registered at the participating hospitals distributed throughout the region. 31 Therefore, our results may at least be generalized to the length of hospital stay after AMI and its predictors in the Osaka region.…”
Section: Study Limitationsmentioning
confidence: 82%
“…However, the subjects registered in the study can be considered representative of the AMI population in the Osaka area, because more than one-third of all AMI patients in Osaka were registered at the participating hospitals distributed throughout the region. 31 Therefore, our results may at least be generalized to the length of hospital stay after AMI and its predictors in the Osaka region.…”
Section: Study Limitationsmentioning
confidence: 82%
“…Kinjo et al suggested socioeconomic factors related to work and lifestyle as an explanation for the secondary peak, especially in young male workers. 19 Because our data did not include such information, we could not analyze the effect of socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The case subjects were 618 patients with AMI who had been enrolled in the Osaka Acute Coronary Insufficiency Study (OACIS; a detailed description of this study has been published elsewhere 20 ). Briefly, we conducted a prospective, multicenter observational study in which 25 collaborating hospitals in the Osaka area recorded demographic, procedural and outcome data on patients with AMI, beginning in April 1998.…”
Section: Case and Control Subjectsmentioning
confidence: 99%